Novel anatomical landmark guided puncture method in L4/L5 spine posterior interlaminar endoscopic surgery: a technical note and case series - Zheng, Bin; Han, Tiepeng; Liang, Yan; Liu, Haiying; Yu, Panfeng (Frontiers in Surgery, 2025)
BackgroundL4/L5 segment lumbar disc herniation and canal stenosis commonly cause low back and leg pain. Posterior interlaminar spine endoscopy has proven efficacy, but puncture positioning relies on experience and requires multiple fluoroscopic exposures, increasing operative difficulty and radiation exposure. This study proposes a vertebral anatomy-based puncture point(Yu Landmark) to assist puncture operations.MethodsA retrospective analysis of 426 L4/L5 posterior interlaminar spine endoscopy patients is conducted, divided into Yu landmark group (205 cases) and conventional group (221 cases). The Yu landmark determines the puncture entry point through the intersection of two lines under anteroposterior fluoroscopy: a vertical line from the midpoint of the L4 inferior articular process and a tangent line from the highest point of the junction between the L4 spinous process base and L4 lamina inferior edge. Puncture efficiency, fluoroscopic usage, complications, and clinical outcomes are compared between groups.ResultsThe Yu landmark group shows significantly reduced fluoroscopic exposures (4.9 ± 1.4 vs. 22.7 ± 4.8), radiation dose (0.48 ± 0.23 vs. 1.34 ± 0.29 mGy), and channel establishment time (22.6 ± 4.7 vs. 29.6 ± 5.9 min) (all P < 0.01), with higher single-puncture success rate (95.1% vs. 82.4%, P < 0.01). Early postoperative VAS and ODI improvements are better, while long-term outcomes and complications are similar.ConclusionsThe Yu landmark is simple, objective, and reproducible, significantly reducing fluoroscopic exposure while improving puncture efficiency, providing a standardized positioning strategy for L4/L5 posterior interlaminar endoscopic surgery.